Health and illness in close relationships - Duggan, Ashley P. (Cambridge : Cambridge University Press, 2020)
Written for academic researchers, students, and health professionals, this is the first volume to review and synthesize the current literature on health and illness in close relationships. The author provides an integrated theoretical framework for understanding the complexities of health trajectories and relationship processes.
Includes bibliographies and index.
Keywords: Psychology; Interpersonal relations; Sick Role